Heaven on Earth: Explaining religious party formation and strength - Fernandes Rebelo, M (2020)
Why do some countries have religious political parties while others do not? And why are religious parties electorally successful in some places but flop at the ballot box in others? This dissertation provides a holistic, integrated explanation of religious party development. Religious parties are formed defensively, in reaction to anticlerical campaigns by state-builders to wrest control of public services like education, poor relief, and healthcare, from religious providers. Once they are formed, the strength of religious parties is determined by the infrastructural power of the state. Weak states that fail to provide adequate public services open up space for religious communities to build a dense civil society network of private schools, hospitals, and charities. Recipients of religious largesse then support confessional parties at the ballot box. By contrast, strong states that provide efficient public services squeeze out private providers of welfare, undermining the electoral strength of religious political parties. I find strong empirical support for this argument in a statistical analysis of religious party formation and strength, using a new dataset on all religious parties that participated in national parliamentary elections between 1800 and 2015. Comparative historical analyses of Québec, Spain, Italy, France, Albania, and Turkey, also back my theoretical arguments. My findings have important implications for the literature on party formation, voting, state-building, and private welfare provision.